Immediate Perinatal Outcome of Mothers with Maternal Near-Miss at Moi Teaching and Referral Hospital, Eldoret, Kenya - David Nding'ori; Winfred Mwangi; Pallavi Mishra; Jack Odunga (European Medical Journal, 2022)
Objective: To compare the immediate perinatal outcome of females with maternal near-miss (MNM) morbidity and those without near-miss morbidity in Moi Teaching and Referral Hospital (MTRH), Eldoret, Kenya. Methods: A case-control study was conducted at MTRH. Near-miss cases were identified using World Health Organization (WHO) criteria for near-miss. A consecutive sampling technique was applied to obtain a total of 45 cases and 225 controls. Determinants of near-miss were assessed using a binary logistic regression model. Perinatal outcomes were compared between the near-miss and control. Results: Severe maternal outcome ratio was 11.4 per 1,000 live births, the MNM ratio was 10.4 per 1,000 live births (95% confidence interval [CI]:7.6-13.9), and MNM mortality ratio was 11.2. The most common condition associated with near-miss was haematological or coagulation dysfunction (64%). Hypertension was the leading underlying cause of near-miss (35%). Factors associated with reduced odds of near-miss were employment (odds ratio: 0.12; 95% CI: 0.03-0.42) and awareness of danger signs (odds ratio: 0.41; 95% CI: 0.19-0.91). Most babies of the near-miss cases were born alive (76%), with median appearance, pulse, grimace, activity, respiration (Apgar) score of 9/10; stillbirth rate was 22%; and median birth weight was 2,700 g. This was similar to the control group with live birth at 77%, a median Apgar score of 9/10, and stillbirth of 23%. There was no statistically significant difference in perinatal outcome between cases and control. Conclusion: MNM indicators are comparable to the world. The determinants of near-miss are unemployment and lack of awareness of danger signs. There was no difference in perinatal outcome between the cases and control.